The impact of semi-natural woodland and pasture on soil properties and streamflow - dataset. - Monger, Felicity; Spracklen, Dominick; Kirkby, Mike; Schofield, Lee (University of Leeds, 2022)
Data from streamflow and soil investigations at RSPB Haweswater, Lake District, UK. Data consists of streamflow, rainfall and soil properties; soil moisture, topsoil permeability, subsoil permeability and bulk density. Data collected in 2018-2020.
Keywords: FOS: Earth and related environmental sciences